Analysis of Production Control, Quality Control, and Total Quality Management Against Product Failure - Miftakul Huda; Wiji Safitri (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
Product quality and productivity are the keys to success for various production systems in the manufacturing world. The phenomenon that occurs in the production process at a manufacturing company located in the Jababeka I Cikarang industrial area is product failure because it does not comply with the standards set by the company. Continuous improvement needs to be done in both production control and quality control, and the implementation of Total Quality Management to reduce the number of product failures and the delivery of OK products to the next process is timely. This study aims to determine how much influence production control and quality control have on the quantity of failed products and how much influence the implementation of total quality management has on Product Failure in the Machining Department. The type of research used is quantitative, and research data were obtained from a sample of 150 respondents. Employees are selected randomly and proportionally in the production department. Data collection includes observation, distributing questionnaires, and literature study. Data processing using the Equation Modeling (SEM) program using the AMOS V.24 program. This study found that Production Control, Quality Control, Total Quality Management have a significant effect on Product Failure. The analysis of the full model shows the study results that the full model meets the goodness of fit. The results of the CR and VE tests showed that the value of (CR & VE) 1st CFA of the Production Control variable (1.0 & 0.9); 1st CFA Quality Control Variable (0.8 & 0.6); 1nd CFA variable Total Quality Management (0.9 & 0.7) and 1nd CFA variable Product Failure (0.7 & 0.6). Hypothesis testing shows results by following under theoretical studies that Production Control, Quality Control, Total Quality Management have a significant effect on Product Failure.